Chloe. 2, The queen of high school - Tessier, Greg (Charmz, 2017)
As she starts ninth grade, Chloe determines to start getting serious about life--school, friends, and family--but, quickly distracted by new technology, things go downhill. For one, her relationship with Alex doesn't seem likely to survive the long-distance factor, and new friends threaten to take time away from her old one.